Kajian Yuridis Laporan Polisi Dalam Perkara Penghinaan Dan/Atau Pencemaran Nama Baik Terhadap Gubernur - Marlen Batlayeri; Reimon Supusepa; Jacob Hattu (TATOHI: Jurnal Ilmu Hukum, 2021)
Introduction: The criminal act of defamation is a legal crime that really needs to be considered because it involves a person's honor and good name. Because it involves a person's honor and good name, the defamation offense is a complaint offense, which means that the report / complaint must be made by the victim himself or the party who feels aggrieved and not from another party. Purposes of the Research: The purpose of this writing is to determine the legal position of the reporter and to know the difference between personal insults and state officials.Methods of the Research: The research method in this writing uses a type of normative research or literature study and is then presented using descriptive research techniques, namely analyzing and explaining the findings of the existing library research..Results of the Research: The results obtained from this research are first, the reporter in the case of insulting and / or defamation against Governor Anies Baswedan does not have a legal position and does not meet the requirements or elements of being a reporter because it is related to an offense of defamation that is a complaint offense. second, based on the elements of defamation offenses contained in the Criminal Code and the ITE Law, the actions of the perpetrators in this case cannot be said to be criminal acts of defamation because Governor Anies Baswedan himself does not feel aggrieved by what the perpetrator has done which can be proven by no report was made by Governor Anies Baswedan Himself.